COMPLIMENT SPEECH ACTS: GENDER REPRESENTATION AND SELF IMAGE OF JISOO BLACKPINK IN INSTAGRAM COMMENT SECTIONS - Fajriani Fitri (Universitas Nias Raya, 2025)
This study examines expressive speech acts of compliment directed at Jisoo Blackpink, using speech act theory and gender representation theory. Using descriptive qualitative research methods and documentation techniques, this study analyzed 100 comments on 8 of Jisoo Blackpink's Instagram posts. The findings show that most of the compliments focused on her physical appearance, self-image, reinforcing traditional gender roles that prioritize beauty over talent. However, some comments also recognized Jisoo's personality and fashion, which are considered very attractive. This study provides insights into how compliments contribute to gender representations and self-image in the comment sections of Jisoo's Instagram posts. It also highlights the complex relationship between beauty, talent and gender in the portrayal of female idols.